Membangun corporate image sektor Perbankan dengan Sentuhan Gerilya Public Relations - Husnia, Nidaul (Maliki Interdisciplinary Journal, 2025)
In an increasingly competitive banking industry, building a strong corporate image is a challenge in itself. Public Relations (PR) plays a key role in creating and maintaining a company image through strategic communication. The two main approaches to PR, Direct Media and Indirect Media, help companies interact with the public directly or through third parties, such as the media and influencers. One PR innovation that is increasingly relevant is Guerrilla Public Relations, which empowers creativity to attract public attention at a more efficient cost. In the banking context, guerrilla PR allows companies to appear more friendly, personal and close to the public, especially through non-conventional campaigns that can create buzz and increase brand awareness. This tactic is effective in reaching a wider audience without appearing too promotional, making it suitable for application in today's digital era. With this approach, banks can build a positive image, increase customer trust, and compete innovatively in an increasingly crowded market.